1997
DOI: 10.1128/jvi.71.1.705-714.1997
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aleutian mink disease parvovirus capsid proteins in defined segments: localization of immunoreactive sites and neutralizing epitopes to specific regions

Abstract: The capsid proteins of the ADV-G isolate of Aleutian mink disease parvovirus (ADV) were expressed in 10 nonoverlapping segments as fusions with maltose-binding protein in pMAL-C2 (pVP1, pVP2a through pVP2i). The constructs were designed to capture the VP1 unique sequence and the portions analogous to the four variable surface loops of canine parvovirus (CPV) in individual fragments (pVP2b, pVP2d, pVP2e, and pVP2g, respectively). The panel of fusion proteins was immunoblotted with sera from mink infected with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 58 publications
4
15
0
Order By: Relevance
“…The presence of a dominant linear epitope is in agreement with the study by Bloom et al . [24]. They located a major linear epitope between amino acids 430 and 525, and also found potential but weaker linear epitopes around presumed AMDV loops 1–3, similar to that found in this study (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The presence of a dominant linear epitope is in agreement with the study by Bloom et al . [24]. They located a major linear epitope between amino acids 430 and 525, and also found potential but weaker linear epitopes around presumed AMDV loops 1–3, similar to that found in this study (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The influence of mink genotype on the immunological recognition of different epitopes was not part of this study, but was investigated by Bloom et al . [24] who found that there was no difference when mink of different genotypes were compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the other AAV epitopes include regions reported to play a role in cellular transduction (reviewed in reference 72). Interestingly, a hypervariable region, which includes residues 208 to 290 (VR-III and VR-IV) of AMDV, serves as a strain-specific epitope (pVP2d) distinguishing the nonpathogenic AMDV-G from the pathogenic AMDV-Utah I strain (73). These residues are localized to the 2-/5-fold wall and 3-fold shoulder of the capsid, similar to what was observed for the HBoV1 strain-specific footprint (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…2A, 5C, and 7). This loop region is a determinant of antibody recognition for other parvoviruses such as adeno-associated virus (AAV), human parvovirus B19, and Aleutian mink disease parvovirus (30,(49)(50)(51). The loop that corresponds to VR-V displays significant differences at both the sequence and structure levels among all three viruses ( Fig.…”
Section: Resultsmentioning
confidence: 99%